ANALISIS KONDISI BISNIS BPRS DALAM MENGANGKAT PASAR INDUSTRI JASA PERBANKAN - Efendi, Rahmat; Mikhriani, Mikhriani (JURNAL MANAJEMEN DAKWAH, 2015)
Today many bank grow in area districtof Sleman. Increasingly fierce competition makes bank are required to further innovate, and have effective strategies in order to achieve customer satisfaction as users of banking service. BPRS MCI is one of the banking institutions located in Sleman, in operation continues to show positive developments it is not independent of market attractiveness and business strength BPRS MCI.The results of this study have implemented BPRS MCI right strategy in accordance with the multifactor approach general electric. This is evidenced by the growing number of customers and impressive profits in each years, product quality and service qualityare increasing. Key Words : Market attractive and business strategy, market banking industry owned by BPRS MCI.